Attitude Towards Online Retailing Services: A Comparison Of Student And Non-Student Samples - Tih, Siohong; Ennis, Sean; M. L. Poon, June (Asian Academy of Management (AAM), 2008)
This study examined the adequacy of using undergraduate student samples in research on online consumer attitudes by comparing the attitudes of students (n = 161) towards online retailing services with the attitudes of non-students (n = 252) towards such services. A structured questionnaire administered online was used to gather data on perceptions, satisfaction, and behavioral intentions with regard to online retailing services. The t-test results showed that, in general, students' attitude towards online retailing services is similar to that of non-students. Therefore, undergraduate students may be reasonable surrogates for consumers in research on online retailing.